Educação e resistência na geração 1980: em busca da utopia necessária - Prado, Maria Noemi Gonçalves do (2006)
The object of this research will be to present the context of the recent Brazilian History, through the 1980 s Generation, recognizing it as a Transitional Generation, making the paradigms, the theoretical perspectives and the slopes of political thought from the end of the twenty century explicit, through the generational intersection that makes it dynamic. Considered by some the Decade of the Political Revival, or the Death of Utopias, for others, it will be in this conflict care that the period of the Decade that Cannot Be Lost will be characterized. To deepen in those premises, concepts were listed as: Generation, Memory, Resistance, Praxis and Utopia, debated by Sociology, Education, Social Psychology, Economy and History, emphasizing, not only, but mainly, the Marxist vision taken by different historical moments and by several theoreticians. To unmask such task we appealed in a panoramic approach to the development of concepts in theoreticians as Mannheim, Halbwachs, Bobbio, organizing the historical contextualization from Hobsbawm, and the Pedagogy discussed by the theoretical vision of Gramsci. The result will be in the development of a field of Praxis and Resistance Culture undertaken by the teachers vanguard, through the multiple axis: Social Movements; Political Movements Unions; reorganization of the reminiscent Left Parties; the foundation of the Workers Party; and the intense debates registered in the core of the Brazilian Intellectuality of the period, standing out in the area of Education Curriculum